Bursting the libraries bubble in Facebook: the challenge of communication - Arroyo-Vázquez, Natalia (Anuario ThinkEPI, 2014)
In general, with few exceptions, libraries are not exploiting the opportunities that Facebook offers, like talking to the users, creating authentic communities or extending their reach. The key element that explains the cause of this deficiency is the way libraries communicate, often modeled on a one-way bulletin board. Several communication objectives that should be incorporated permanently into the social media strategy of the library, and some ideas to improve the performance in Facebook, are provided. To be successful, libraries must know and adapt to the medium, and try to meet users´ interests.